Motivation Affecting Work Efficiency of Company Employees in Nonthaburi Province - หมื่นหาญ ประทีป; ศิลป์วิเศษสรรค์ กุสุมา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to 1) study the motivation level of employees in Nonthaburi Province, 2) study the performance level of employees in Nonthaburi Province, 3) compare the performance of employees in Nonthaburi Province, and 4) 4. Personal factors affecting the performance of employees in Nonthaburi Province. The sample group used in this research was 400 employees in Nonthaburi Province. A questionnaire was used as the data collection tool. The data were analyzed using descriptive statistics. The statistics used in the research were frequency, percentage, mean, and standard deviation (S.D.). One-way Anova was used. The Scheffe’s test for pairwise differences was performed at a statistical significance level of 0.05 The results of the research found that the sample of employees in Nonthaburi Province who responded to the questionnaire were mostly female, aged 20-30 years, held operational positions, had completed high school, and had a vocational certificate. The average income is between 10,000-15,000 baht. The working period is less than 5 years. From the hypothesis testing, it was found that different ages have different work efficiency. Gender, education level, monthly income, job position, and different work years have no different work efficiency. The statistical significance is 0.05. The 5 work factors affect the work efficiency of the employees at a high level. The analysis of work efficiency in all 4 areas is at a high level. When considering, it is found that it is at a high level in all areas: work quantity, work quality, work speed, and expenses.